Intrinsically Chiral Twist‐Bend Nematogens: Interplay of Molecular and Structural Chirality in the NTB Phase. Issue 6 (14th March 2023) - Walker, Rebecca; Pociecha, Damian; Salamonczyk, Miroslaw; Storey, John M. D.; Gorecka, Ewa; Imrie, Corrie T.
Abstract: The front cover artwork is provided by Dr Rebecca Walker of the Liquid Crystals Group at the University of Aberdeen. The image is a cartoon depiction of the formation of the heliconical chiral twist‐bend nematic phase (N*TB ) from its constituent bent molecules. The presence of a single enantiomer of the chiral, lactate‐based liquid crystal dimers biases the formation of helices with only one handedness, unlike in the conventional NTB phase, observed for achiral molecules, for which the left‐ and right‐handed helices are doubly degenerate. Read the full text of the Research Article at 10.1002/cphc.202200807 . Abstract : "We report bent liquid crystal dimers containing the lactate group. In these dimers, the spacer contains an odd number of atoms connecting the two mesogenic units and this imparts the molecular curvature required for the observation of twist‐bend phases. In order to facilitate the comparison between the chiral and racemic systems, we also prepare a single racemic dimer…" This and more about the story behind the front cover can be found in the Research Article at 10.1002/cphc.202200807 .